2012
DOI: 10.1371/journal.pone.0051691
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Stones: Evidence of a Specific Chemistry Related to Infection and Presence of Bacterial Imprints

Abstract: Prostatic stones are a common condition in older men in industrialized countries. However, aging appears not to be the unique pathogenesis of these calcifications. Our morpho-constitutional investigation of 23 stone samples suggested that infection has a significant role in the lithogenic process of prostate calcifications, even without detection of infection by clinical investigation. Most stones (83%) showed bacterial imprints and/or chemical composition, suggestive of a long-term infection process. Chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 29 publications
(31 reference statements)
2
45
0
8
Order By: Relevance
“…Regarding ethics, we follow the usual procedures Dessombz et al, 2012). All participants (adults or parents of children participating in the study) gave their verbal consent, documented by the researchers, for use of the material.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding ethics, we follow the usual procedures Dessombz et al, 2012). All participants (adults or parents of children participating in the study) gave their verbal consent, documented by the researchers, for use of the material.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of prostate stones is different, as calcium oxalate monohydrate and dihydrate, brushite, whitlockite, octocalcium phosphate, and amorphous calcium phosphate have been reported [10, 11]. However, the use of more reliable methods, such as infrared spectroscopy, has shown that the more characteristic phase of prostate stones is carbapatite that is commonly associated with the presence of infection and alkaline urine [12]. On the other hand, Scanning Electron Microscope has demonstrated a high frequency of bacterial imprints in prostate stones [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of more reliable methods, such as infrared spectroscopy, has shown that the more characteristic phase of prostate stones is carbapatite that is commonly associated with the presence of infection and alkaline urine [12]. On the other hand, Scanning Electron Microscope has demonstrated a high frequency of bacterial imprints in prostate stones [12]. Lastly, the chemical analysis of prostate fluid composition had shown that the concentration of citrates decreases dramatically in the presence of infection [13-15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies showed that acute phase proteins predominated in the structure of prostatic stones [25,26] . In addition, bacterial biofilm was found in the prostatic stones and high frequency of bacterial imprints was found in these stones by electron microscopy scanning [27][28][29] . Results of the study by Kim et al [4] support these findings, since they showed that prostatic stones could be influenced by antimicrobial therapy in patients with chronic bacterial prostatitis.…”
Section: Discussionmentioning
confidence: 99%